The Kairos of Information Literacy as Professional Practice - Drabinski, Emily (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2016)
Using kairos as an analytic lens, this paper examines the debate around ACRL’s Framework for Information Literacy as action married to time. Rather than leading librarians inexorably to the true meaning of information literacy, kairos surfaces a discourse of the exceptional present as productive instead of the profession itself. Cette étude s’appuie sur la notion de kairos comme angle d’analyse pour examiner le débat autour de la proposition de l’ACRL concernant la compétence informationnelle comme action mariée au temps. Au lieu de mener inexorablement les bibliothécaires à la vraie signification de la compétence informationnelle, le kairos fait émerger un discours où le présent exceptionnel est productif en lieu et place de la profession elle-même. *** Awarded 2015 Best Practitioner Paper ***